2004
DOI: 10.1146/annurev.matsci.34.040203.121025
|View full text |Cite
|
Sign up to set email alerts
|

Materials Assembly and Formation Using Engineered Polypeptides

Abstract: ▪ Abstract  Molecular biomimetics can be defined as mimicking function, synthesis, or structure of materials and systems at the molecular scale using biological pathways. Here, inorganic-binding polypeptides are used as molecular building blocks to control assembly and formation of functional inorganic and hybrid materials and systems for nano- and nanobiotechnology applications. These polypeptides are selected via phage or cell surface display technologies and modified by molecular biology to tailor their bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
253
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 241 publications
(254 citation statements)
references
References 112 publications
1
253
0
Order By: Relevance
“…Further, combining these types of linkers in one experiment can allow different orthogonally-targeted biomolecules to be self-assembled with the same QD to create multifunctional probes. Alternatively, switching the peptide sequences to those that recognize other metals or semiconductors can potentially allow selfassembly of similar biomolecules with a variety of other nanoparticle surfaces [30]. Lastly, it is also worth mentioning that several recent studies have suggested that it is possible to self-assemble polyhistidine modified proteins and peptides with commercial QD preparations [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Further, combining these types of linkers in one experiment can allow different orthogonally-targeted biomolecules to be self-assembled with the same QD to create multifunctional probes. Alternatively, switching the peptide sequences to those that recognize other metals or semiconductors can potentially allow selfassembly of similar biomolecules with a variety of other nanoparticle surfaces [30]. Lastly, it is also worth mentioning that several recent studies have suggested that it is possible to self-assemble polyhistidine modified proteins and peptides with commercial QD preparations [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…[61][62][63][64][65] Among the display technologies, the in vivo selection of peptides using cellsurface display (CSD) and phage display (PD) has been used most frequently (Figure 2). 9 CSD is a technology whereby peptides appear on the flagella of a bacterial cell membrane. PD is a technology whereby peptides appear on the coat protein of a phage.…”
Section: Selection Of Inorganic-binding Peptides Using Combinatorial mentioning
confidence: 99%
“…These approaches have been adapted to select peptides that bind to solid inorganic materials. 1,[3][4][5][6][7][8][9][55][56][57][58][59]66 The articles by Evans et al and Tomczak et al in this issue explain combinatorial mutagenesis, the method of creating a large set of phage or bacteria-each displaying a peptide with a random sequence-and the biopanning process, the method that culls the set to obtain only the peptide sequences that selectively bind The enamel has an architecture of woven enamel rods (3 µm diameter) at the micrometer scale, each rod containing thousands of long HA crystallites (10s of nm thick and several mm long), all spatially and crystallographically well-organized on the nanometer scale.…”
Section: Selection Of Inorganic-binding Peptides Using Combinatorial mentioning
confidence: 99%
See 2 more Smart Citations